Food selection of maize weevil Sitophilus Zeamais (motschulsky) - Dzuong, Nguyen Van; Long, Khuat Dang (Academia Journal of Biology, 2020)
The instintive behaviour exhibited by insects in the selecting food is always a matter of interests to entomologists, and it is one of the fundamental principles underlining the application of entomology to agriculture, horticulture and forestry. Food seclection is an important characteristic of insects that help them survive in periods with insufficient foods. Three grain types of food, maize grain, long-grain rice and soybean grain, were used in this sudy for detecting food selection behaviours of maize weevil, Sitophilus zeamais. Grains were kept in box traps put in the different stores in Son La during 90 days. The result showed that maize weevil, Sitophilus zeamais, prefered traps with maize grains (71.4%) considerably more than ones with long-grain rice (14.3%) and soybean grain (14.3%). Meanwhile, the cornsap beetle, Carpophilus dimidiatus, was mostly observed in maize grain (98.5%) and to a lesser degree, in soybean grain (1.5%); and the dried-fruit beetle, Carpophilus hemipterus, was abundantly observed in maize grain (93.1%) and less in soybean grain (6.9%). The red flour, Tribolium castaneum, also tended to select all the three food grain, i.e. maize grain: 53.5%, long-rice grain: 35.2%, and soybean grain: 11.3%. Comparing f beetle individuals captured on three types of food grains showed that the maize weevil, Sitophilus zeamais, is the most abundant species. The percentage this store beetle among all beetles observed in maize, soybean grains and long-rice grains were 57.0%, 84.9% and 27.6%, respectively. Interestingly, Ahasverus advena, foreign grain beetle, occurred abundantly on long-rice gain (61.7%), i.e. this grain is a suitable food for the development of this beetle.